ON THE REPRESENTATION OF FUNCTIONS BY SERIES OFLEGANDRE POLYNOMIALS IN WEIGHTED $ L_μ ^q[-1, 1]$ SPACES - Grigorian, M. G.; Sargsyan, A. S. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2001)
In this paper we construct the weighted  $L_\mu ^q[-1, 1],  q \in[1, 4/3]\cup [4, +\infty],$ and Legander series $\sum \limits_{k=1} ^\infty c_pP_k(x)$, which is universal in $L_\mu ^q [-1, 1]$.